Micro-sized thin-film solar cells via area-selective electrochemical deposition for concentrator photovoltaics application - Siopa, Daniel (Sci Rep, 2020)
Micro-concentrator solar cells enable higher power conversion efficiencies and material savings when compared to large-area non-concentrated solar cells. In this study, we use materials-efficient area-selective electrodeposition of the metallic elements, coupled with selenium reactive annealing, to form Cu(In,Ga)Se(2) semiconductor absorber layers in patterned microelectrode arrays. This process achieves significant material savings of the low-abundance elements. The resulting copper-poor micro-absorber layers’ composition and homogeneity depend on the deposition charge, where higher charge leads to greater inhomogeneity in the Cu/In ratio and to a patchy presence of a CuIn(5)Se(8) OVC phase. Photovoltaic devices show open-circuit voltages of up to 525 mV under a concentration factor of 18 ×, which is larger than other reported Cu(In,Ga)Se(2) micro-solar cells fabricated by materials-efficient methods. Furthermore, a single micro-solar cell device, measured under light concentration, displayed a power conversion efficiency of 5% under a concentration factor of 33 ×. These results show the potential of the presented method to assemble micro-concentrator photovoltaic devices, which operate at higher efficiencies while using light concentration.